In vitro cytotoxicity evaluation of locally produced dental porcelain - Husein, Adam (Pusat Pengajian Sains Pergigian Universiti Sains Malaysia, 2011)
The in vitro cytotoxic potential of locally produced dental porcelain was evaluated in this study. The cellular response of human osteoblast and MRC-5 cell lines were assessed using MTT assay by incubatiog with the fluid extract of dental porcelain powder and dental porcelain discs (direct test). Aging process was carried out by submerging the discs into 3% Bovine Serum Albumin (BSA) solution. Tests on extracts showed that the material was significantly different from the control at a concentration of 250 mg/ml. Direct test showed thRt the material after aging was not significantly different from the control with a mean (SD) of 89.2(13.4) %, whereas, it was significantly different from the control before conditioning of BSA with a mean (SD) of 88.5(12.1) %. However, the dental porcelain caused mild suppression of succinate dehydrogenase activity (<25%), which is considered to be accepted clinically and hence can be ranked as being non-cytotoxic or mildly cytotoxic.